Acupressure to Increase Milk Production in Breastfeeding Moms - Kustiyati, Sri; Ningrum, Ari Kusuma (P3M Universitas 'Aisyiyah Surakarta, 2024)
Introduction: Giving acupressure therapy can increase breast milk production because it affects the stimulation process of the hormone prolactin. This study aimed to determine the effect of acupressure at points ST 15, ST 16, and Li 4 on breast milk production in postpartum mothers. Materials and Method: Type of quantitative research. Quasi-experimental research design, post-test control group research design. The sample was 32 people, 16 in the control group and 16 in the treatment group. Data processing and analysis using the SPSS application with the Mann-Whithney test. Result: The Mann-Whitney test output obtained a p-value of 0.000 (<0.05). The group of postpartum mothers who were treated produced more breast milk than the group who were not treated. Conclusion: Acupressure at points ST 15, ST 16 and, Li 4 can increase breast milk production in postpartum mothers. Midwives can perform acupressure at points ST 15, ST 16, and Li 4 on postpartum mothers to increase breast milk production.